Tissue-type Plasminogen Activator –7,351C/T Enhancer Polymorphism Is Associated with a First Myocardial Infarction - Ladenvall, Per; Johansson, Lars; Jansson, Jan-Håkan; Jern, Sverker; Nilsson, Torbjörn K.; Tjärnlund, Anna; Jern, Christina; Boman, Kurt (Thrombosis and Haemostasis, 2002)
We recently identified a polymorphic Sp1 binding site in an enhancer at the tissue-type plasminogen activator (tPA) locus (tPA –7,351C/T), which was associated with vascular tPA release. Subjects homozygous for the –7,351C allele had twice the tPA release rate compared to subjects carrying the –7,351T allele. In this study we tested the hypothesis that the tPA –7,351C/T polymorphism is associated with myocardial infarction (MI). In a population-based prospective nested case-control study within northern Sweden, genotypes were determined among 61 MI cases and 120 controls. In a multivariate model, the tPA –7,351C/T polymorphism (OR 2.68 for T allele carriers; 95% CI 1.31– 5.50), tPA antigen (OR 1.16; 95% CI 1.07–1.25) and apo A-I (OR, 0.997; 95% CI 0.995–0.999) were independently associated with a first MI. These findings suggest that genetic markers of local tPA release and circulating steady-state tPA levels carry independent prognostic information.
Keywords: Myocardial infarction; tissue-type plasminogen activator; enhancer; polymorphism